2018
DOI: 10.3389/fimmu.2018.00364
|View full text |Cite
|
Sign up to set email alerts
|

The MEK1/2-ERK Pathway Inhibits Type I IFN Production in Plasmacytoid Dendritic Cells

Abstract: Recent studies have reported that the crosslinking of regulatory receptors (RRs), such as blood dendritic cell antigen 2 (BDCA-2) (CD303) or ILT7 (CD85g), of plasmacytoid dendritic cells (pDCs) efficiently suppresses the production of type I interferons (IFN-I, α/β/ω) and other cytokines in response to toll-like receptor 7 and 9 (TLR7/9) ligands. The exact mechanism of how this B cell receptor (BCR)-like signaling blocks TLR7/9-mediated IFN-I production is unknown. Here, we stimulated BCR-like signaling by lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…We observed that the TLR7-dependent increase in FOSL1 expression was dependent on both (99) and FOSL1 (72). Moreover, the absence of type I IFN expression upon TLR7 stimulation had previously been observed in human macrophages upon HCV infection (14) and in human dendritic cells upon Influenza infection or small molecule activation(100).…”
Section: Discussionsupporting
confidence: 63%
“…We observed that the TLR7-dependent increase in FOSL1 expression was dependent on both (99) and FOSL1 (72). Moreover, the absence of type I IFN expression upon TLR7 stimulation had previously been observed in human macrophages upon HCV infection (14) and in human dendritic cells upon Influenza infection or small molecule activation(100).…”
Section: Discussionsupporting
confidence: 63%
“…Mitogen activated protein kinases, including ERK1/2 and JNK1/2 signalling pathways, have also been implicated in IFN production in response to TLR activation . Inhibition of SphK1 attenuated activation of these signalling pathways during TLR stimulation (Figures E and S3C).…”
Section: Resultsmentioning
confidence: 97%
“…Cross-linking of the Ig-like transcript ILT7 and the transmembrane adapter FcεRIg on primary human PDCs inhibited IFN-a production (92). CD303 (BDCA-2) can also directly bind FcεRIg and activated a novel BCR-like signaling pathway suppressing IFN-a production (93,94). Either of the inhibitory pathways may be responsible for dampened IFN-a production by tonsil PDCs via mechanisms currently unknown.…”
Section: Discussionmentioning
confidence: 99%